A culturally proficient society begins in school : leadership for equity - Franco, Carmella S.; Ott, Maria G.; Robles, Darline P.; Lindsey, Randall B.; Graham, Stephanie M. (Thousand Oaks, Calif. : Corwin Press, 2011)
'This book is about the American Educational Dream and how all educators can be successful with students from diverse cultural backgrounds. Written by three Latina superintendents who have achieved great success as leaders of culturally and linguistically-diverse districts, the book provides a unique vision for transforming schools into places of equity and excellence. The authors use the lens of Cultural Proficiency to facilitate an understanding of both the barriers to educational opportunity as well the conditions that help to promote the success of underserved groups. Their lessons for being successful in diverse communities are a source of inspiration to all educators who aspire to extend the promises of democracy to every public school student'-- Provided by publisher.
Machine generated contents note: AcknowledgmentsAbout the AuthorsIntroduction1. The Why of This Book2. Pueblo, Kronach and East Los Angeles Our Beginnings3. Conversation with the Superintendents: The Teacher Years4. Conversation with the Superintendents: The Administrative Years5. Lessons Learned: Acknowledging Barriers, Recognizing Cultural Assets6. Lessons Learned: Cultural Assets Inform Actions7. Developing Your Leadership for Equity PlanResourcesReferencesIndex.
Includes bibliographical references and index.
Keywords: School management and organization -- Social aspects -- United States; Multicultural education -- United States; Educational equalization -- United States; School improvement programs -- United States